Electronic Medical Record Management of Top 10 Outpatient Diseases Using the Waterfall Method - Oktaviana, Rizki Salma; Anisha, Selly Puji; Syahidin, Yuda; Sari, Irda (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
This study aims to describe several problems related to data processing of the top 10 outpatient diseases. The research method used is a qualitative research method with a descriptive approach and a waterfall software development method, while the data collection techniques used are observation and interviews with medical record staff. In the research, problems were found such as diagnoses that were difficult to read by poly officers, the existence of duplicate tasks for medical record officers and recording still using manuals filled in by poly officers which were then inputted into the Microsoft Office Excel program and only made worksheets to then be processed back into the top 10 outpatient disease reports. The suggestions given for problem solving are the coordination between officers and doctors regarding the writing of diagnoses, the addition of medical record officers to reduce the workload and the design of a software that can facilitate the process of processing data on the top 10 outpatient diseases using Visual Studio 2012. So that the final report on the top 10 diseases can be accurate and can improve the quality of service in the hospital.